Exploring the effect of previous inactivated influenza vaccination on seasonal influenza vaccine effectiveness against medically attended influenza: Results of the European I‐MOVE multicentre test‐negative case‐control study, 2011/2012‐2016/2017. Issue 5 (9th May 2018) - Valenciano, Marta; Kissling, Esther; Larrauri, Amparo; Nunes, Baltazar; Pitigoi, Daniela; O'Donnell, Joan; Reuss, Annicka; Horváth, Judit Krisztina; Paradowska‐Stankiewicz, Iwona; Rizzo, Caterina; Falchi, Alessandra; Daviaud, Isabelle; et al.
Abstract : Background: Results of previous influenza vaccination effects on current season influenza vaccine effectiveness (VE) are inconsistent. Objectives: To explore previous influenza vaccination effects on current season VE among population targeted for vaccination. Methods: We used 2011/2012 to 2016/2017 I‐MOVE primary care multicentre test‐negative data. For each season, we compared current season adjusted VE (aVE) between individuals vaccinated and unvaccinated in previous season. Using unvaccinated in both seasons as a reference, we then compared aVE between vaccinated in both seasons, current only, and previous only. Results: We included 941, 2645 and 959 influenza‐like illness patients positive for influenza A(H1N1)pdm09, A(H3N2) and B, respectively, and 5532 controls. In 2011/2012, 2014/2015 and 2016/2017, A(H3N2) aVE point estimates among those vaccinated in previous season were −68%, −21% and −19%, respectively; among unvaccinated in previous season, these were 33%, 48% and 46%, respectively (aVE not computable for influenza A(H1N1)pdm09 and B). Compared to current season vaccination only, VE for both seasons' vaccination was (i) similar in two of four seasons for A(H3N2) (absolute difference [ad] 6% and 8%); (ii) lower in three of four seasons for influenza A(H1N1)pdm09 (ad 18%, 26% and 29%), in two seasons for influenza A(H3N2) (ad 27% and 39%) and in two of three seasons for influenza B (ad 26% and 37%); (iii) higher in one season for influenza A(H1N1)pdm09 (ad 20%) and influenza B (ad 24%). Conclusions: We did not identify any pattern of previous influenza vaccination effect. Prospective cohort studies documenting influenza infections, vaccinations and vaccine types are needed to understand previous influenza vaccinations' effects.